Expression of Leadership Skills of Music Teacher - Talalienė, Živilė; Šečkuvienė, Henrika (Pedagogika, 2015)
Leadership in contemporary society is perceived as a process, which contributes to efficient solution of constantly emerging problems in business, pedagogical and social spheres. Over the last period a rapid progress of science and various technologies has been observed and leadership has acquired a significant status in education as well. To make leadership a natural phenomenon at school, there is a need for a harmoniously functioning link: authorities-leaders; teachers - leaders, who should educate a new generation of school learners-leaders. A teacher of music or a leader of music collective has to rally school learners for attainment of common goals: to develop music abilities during lessons of music; to satisfy needs for music expression during non-formal activities. Therefore, this mission may be implemented only by a teacher-leader. The object of the research: leadership skills of music teacher. The goal of the research: to reveal peculiarities of expression of music teacher’s leadership skills. The research methods: analysis of scientific literature, semi-structured interview, qualitative content analysis. The analysis of scientific literature on leadership issues was carried out during the research and leadership skills that are most characteristic of music teachers were highlighted. On the basis of the distinguished abilities, the model of expression of leadership skills of music teacher of general education school was designed. The semi-structured interview was conducted and its sample included six respondents. The data acquired during the interview were processed employing the qualitative content analysis. The results of the research showed that the identified leadership skills of music teacher may be characterised through the following features: • Motivation (inspiration) for music activities is manifested during lessons and extracurriculum music activities. • Communication and collaboration is seen through joint activities with teachers of other study subjects, administration and learners’ parents. Successful communication is predetermined by friendly, sincere, mutual and responsible style of communication. • Ability to solve problems that emerge during music activities is revealed through collaboration with class master, colleagues and specialists, clarification of situation, individual conversations, sincere communication, professional attitude, understanding of group needs, prioritising of the goal to be attained over personal needs. • Management of stressful situations is expressed through recognition of conflict situations, application of various conflict resolution ways, control of emotions, positive attitude and understanding of behaviour, which typical of a certain age group of a learner. The research results showed that leadership skills are very important to successful activities of a music teacher because a music teacher-leader has a vision and able to rally children for joint music activities to achieve as good results as possible.